Pseudoxanthoma elasticum at Hue Central Hospital - Trang, Nguyen Thi Thuy; Xuan, Nguyen Thanh; Linh, Le Phan Hai; Thao, Pham Nguyen Da; Tram, Tran Le Bao; Hao, Mai Xuan (Tạp chí Y học lâm sàng Bệnh viện Trung Ương Huế, 2025)
Background: Pseudoxanthoma Elasticum (PXE) is a rare disease with autosomal recessive inheritance. Dysfunctional or absent ABCC6 results in low serum pyrophosphate (PPi) and ectopic calcification, particularly affecting elastic tissue, eyes, and blood vessels. Clinical signs of PXE usually begin in early childhood, with skin changes often being the first indication. These lesions progress slowly and are associated with risks of blindness and peripheral vascular compromise. We present a case of a male patient diagnosed with Pseudoxanthoma Elasticum at Hue Central Hospital. Case report: A 20-year-old male patient presented with skin lesions that began at age 13. Initially, small flesh-colored papules appeared in the periumbilical and abdominal areas, gradually coalescing into larger papules or plaques symmetrically located across the abdomen, chest, armpits, arms, and groins. The lesions progressed slowly over the years without inflammation or ulceration, and the patient reported no pain or itching. A skin biopsy indicated Pseudoxanthoma Elasticum, leading to referrals for further evaluation. Conclusion: Early recognition of PXE is crucial due to its association with significant health risks. Prompt diagnosis allows for preventive measures and monitoring to control disease progression.